Shallot vs. Dadap Serep leaf compresses: Non-pharmacological approaches to fever management in toddlers with ARIs - Mulyati, Leli; Septiansah, Hendra; Haryani, Sri; Camilla, Vhebyta; Sasmito, Priyo (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Fever is one of the most common symptoms of Acute Respiratory Infections (ARIs) in toddlers, and non-pharmacological interventions such as traditional compresses are widely used in community settings. Shallot (Allium cepa L) compresses and dadap serep (Erythrina subumbrans) leaf compresses are two conventional methods believed to have antipyretic effects, yet direct comparative evidence remains limited. Purpose: To compare the effectiveness of shallot compresses and dadap serep leaf compresses in reducing fever among toddlers diagnosed with ARIs. Method: A quasi-experimental design with a pre-test and post-test control group was employed. A total of 34 toddlers aged 12–59 months were selected using purposive sampling and evenly divided into two groups: shallot compress (n = 17) and dadap serep compress (n = 17). Body temperature was measured before and 15 minutes after the intervention. Data were analyzed using paired t-tests, independent t-tests, and N-Gain scores. Results: Both interventions significantly reduced body temperature (p < 0.001). The dadap serep group showed a slightly higher absolute temperature reduction (0.60°C) compared to the shallot group (0.50°C). However, the shallot compress demonstrated a higher N-Gain score, indicating greater proportional effectiveness. Conclusion: Shallot and dadap serep leaf compresses are both effective, low-cost, and accessible non-pharmacological interventions for reducing fever in toddlers with ARIs. Shallot compresses provide more stable proportional effectiveness, while dadap serep compresses offer a slightly greater immediate reduction. Both methods hold value for home-based fever management and primary healthcare settings.